Immunogenicity evaluation of MS2 phage-mediated chimeric nanoparticle displaying an immunodominant B cell epitope of foot-and-mouth disease virus - Wang, Guoqiang; Liu, Yunchao; Feng, Hua; Chen, Yumei; Yang, Suzhen; Wei, Qiang; Wang, Juan; Liu, Dongmin; Zhang, Gaiping (PeerJ, 2018)
Foot-and-mouth disease (FMD) is a highly contagious disease of cloven-hoofed animals that has caused tremendous economic losses worldwide. In this study, we designed a chimeric nanoparticles (CNPs) vaccine that displays the predominant epitope of the serotype O foot-and-mouth disease virus (FMDV) VP1 131-160 on the surface of MS2 phage. The recombinant protein was expressed in Escherichia Coli and can self-assemble into CNPs with diameter at 25–30 nm in vitro. A tandem repeat peptide epitopes (TRE) was prepared as control. Mice were immunized with CNPs, TRE and commercialized synthetic peptide vaccines (PepVac), respectively. The ELISA results showed that CNPs stimulated a little higher specific antibody levels to PepVac, but was significantly higher than the TRE groups. Moreover, the results from specific IFN-γ responses and lymphocyte proliferation test indicated that CNP immunized mice exhibited significantly enhanced cellular immune response compared to TRE. These results suggested that the CNPs constructed in current study could be a potential alternative vaccine in future FMDV control.
Keywords: Foot-and-mouth disease virus; Chimeric nanoparticles; MS2 bacteriophage; G-H loop